A Unique and Rare Presentation of Adult Congenital Heart Disease: Common Atrium Associated with Coronary Aneurysms and Fistula - Muhammad Shabbir Rawala; Alex Munoz; Mohammad Hassan Pervaiz (Case Reports in Cardiology)
An atrial septal defect is the second most common congenital heart disease found in adults with a female to male ratio of 4 : 1. However, it is rare to have a complete absence of the interatrial septum (IAS) to be diagnosed in an elderly patient associated with other coexisting anomalies. We present a case of a 60-year-old female presenting with common atrium, coronary arteriovenous fistula, and coronary artery aneurysms. This case highlights rare adult congenital cardiac anomalies and the importance of thorough workup to evaluate for the intracardiac shunt in a patient who has right heart enlargement and development of pulmonary disease in adulthood without a significant history of chronic smoking. A 60-year-old female patient presented with substernal chest pain. The nuclear stress test showed no reversible ischemia; however, right ventricle (RV) dilation was present. The patient underwent further evaluation for RV dilation with a transthoracic echocardiogram that demonstrated a complete absence of IAS and was confirmed by a positive bubble study. The patient had an invasive angiography that showed severely elevated RV pressure. Oxygen saturation in the right atrium was higher than in the inferior vena cava. Hence, an intracardiac shunt with a 10% increase in oxygen saturation was identified. It also identified aneurysmal coronary arteries (measuring 0.8 to 1.0 cm). Cardiac computed tomography angiogram was performed that identified all coronary arteries to be ectatic/aneurysmal measuring up to 8-10 mm, an absence of IAS, and a possible fistula between the distal left anterior descending and a coronary vein. To our knowledge, this is the first-ever presentation of a complete congenital absence of IAS in a patient who has survived into adulthood with the development of severe pulmonary hypertension without Eisenmenger syndrome. It is unclear at this point if surgical treatment to correct the anatomical defect (which would be probably palliative) would be superior to conservative medical therapy. Besides, the presence of coronary arteriovenous fistula would make the decision-making process more complex regarding surgical versus conservative management.